Use of cervicovaginal PAMG-1 protein as a predictor of delivery within seven days in pregnancies at risk of premature birth - Yasemin Çekmez; Gürkan Kıran; Esra Tuştaş Haberal; Merve Dizdar (BMC, 2017)
Abstract Background To investigate the utility of vaginal placental alpha microglobulin-1 (PAMG-1) protein as a predictor of preterm delivery within 7 days in pregnancies at risk of premature birth. Methods This prospective study was performed in women at risk of premature birth. The levels of vaginal PAMG-1 and foetal fibronectin (fFN) and the transvaginal cervical length measurement (CLM) were investigated and compared. Results Seventy-two pregnant women were included in this study. The sensitivities of PAMG-1, fFN and CLM were 73.3, 73.6%, and 52.9%, respectively, while the specificities of PAMG-1, fFN and CLM were 92.9%, 94.3%, and 90.9%, respectively. The positive predictive values of PAMG-1, fFN and CLM were 73.3%, 82.3%, and 64.2%, respectively, and the negative predictive values of PAMG-1, fFN and CLM were 92.9%, 90.9%, and 86.2%, respectively. Conclusion The diagnostic accuracy of PAMG-1 is similar to that of fFN in terms of preterm labour detection within 7 days.